Conceptualisations of masculinity and sexual development among boys and young men in Korogocho slum in Kenya. Issue 2 (1st February 2022) - Maina, Beatrice W.; Sikweyiya, Yandisa; Ferguson, Laura; Kabiru, Caroline W.
Abstract: Youth and adolescence are times when young men negotiate their identity in relation to social and cultural expectations of being a man, with enduring implications for sexual health and wellbeing. This study explored how boys aged 10–14 years living in Korogocho slum in Nairobi, Kenya conceptualised masculinity, their perceptions of how masculinities are performed, and the linkage between conceptualisations of masculinity and sexual development. Three bases of gender socialisation were identified: (1) verbal messaging (mainly from parents and teachers); (2) observing the behaviours of older men in the community; and (3) information received from mainstream and social media. Masculinity conceptualisations focussed on financial stability, family life and responsibility, physical attributes, character and religion. Two contrasting portrayals of masculinity emerged in the form of idealised and dominant masculinities. A close linkage was found between masculinity conceptualisations and sexual development. Findings are important for programmes that aim to transform harmful gender norms and signal the need for longitudinal research exploring how gender beliefs may change over time.